Anodic stripping voltammetry of arsenic(III) using gold nanoparticle-modified electrodes. - Dai, X; Nekrassova, O; Hyde, M; Compton, R (2004)
A novel method for the detection of arsenic(III) in 1 M HCl at a gold nanoparticle-modified glassy carbon electrode has been developed. The gold nanoparticles were electrodeposited onto the glassy carbon electrode via a potential step from +1.055 to -0.045 V vs SCE for 15 s from 0.5 M H2SO4 containing 0.1 mM HAuCl4. The resulting electrode surfaces were characterized with both AFM and cyclic voltammetry. Anodic stripping voltammetry of arsenic(III) on the modified electrode was performed. After optimization, a LOD of 0.0096 ppb was obtained with LSV.